2011
DOI: 10.1161/hypertensionaha.111.171488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Reduction in Uric Acid on Renal Outcomes During Losartan Treatment

Abstract: Abstract-Emerging data show that increased serum uric acid (SUA) concentration is an independent risk factor for end-stage renal disease. Treatment with the antihypertensive drug losartan lowers SUA. Whether reductions in SUA during losartan therapy are associated with renoprotection is unclear. We therefore tested this hypothesis. In a post hoc analysis of 1342 patients with type 2 diabetes mellitus and nephropathy participating in the Reduction of Endpoints in Non-Insulin-Dependent Diabetes Mellitus With the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(64 citation statements)
references
References 27 publications
4
53
1
1
Order By: Relevance
“…SUA is an independent risk factor for CKD, even without diabetes [57] . SUA is known to be associated with disease progression in the early stage of diabetic nephropathy [17,58] . We found that the progression of renal dysfunction in patients with type 2 diabetic overt nephropathy with an SUA concentration of ≥ 6.3 mg/dL carries a poor prognosis, even though their SUA range is considered high-normal [59] .…”
Section: Nephropathymentioning
confidence: 99%
“…SUA is an independent risk factor for CKD, even without diabetes [57] . SUA is known to be associated with disease progression in the early stage of diabetic nephropathy [17,58] . We found that the progression of renal dysfunction in patients with type 2 diabetic overt nephropathy with an SUA concentration of ≥ 6.3 mg/dL carries a poor prognosis, even though their SUA range is considered high-normal [59] .…”
Section: Nephropathymentioning
confidence: 99%
“…More recently, the angiotensin-receptor blocker losartan has been shown to decrease serum uric acid in a group of patients with type 2 diabetes and nephropathy, and this reduction was associated with a reduction in CKD progression. 23 ETreceptor antagonism offers a potentially novel approach to decreasing serum uric acid in patients with proteinuric CKD.…”
mentioning
confidence: 99%
“…Although beyond the scope of this review, other clinically meaningful results unrelated to gout manifestations have been reported. Losartan has demonstrated renoprotective effects directly related to the degree of serum uric acid lowering; however, these endpoints were not explored in the included studies that enrolled patients with baseline hyperuricemia or a gout diagnosis [Ito et al 2012;Miao et al 2011].…”
Section: Discussionmentioning
confidence: 99%